Thermal effective Lagrangian of generalized electrodynamics in static gravitational fields - Bufalo, R. [UNESP] (Amer Physical Soc, 2014)
In this paper we compute the effective Lagrangian of static gravitational fields interacting with thermal fields of generalized electrodynamics at high temperature. We employ the usual Matsubara imaginary-time formalism to obtain a closed form expression to the thermal effective Lagrangian at one-loop and two-loop order, in an arbitrary omega-dimensional spacetime, in which the equivalence between the static hard thermal loops and those with zero external energy momentum is widely explored. Afterwards, the symmetries of the resulting expressions are discussed as well as the presence of the Tolman local temperature.